2013
DOI: 10.15451/ec2013-8-2.3-1-05
|View full text |Cite
|
Sign up to set email alerts
|

Why is change feared? Exotic species in traditional pharmacopoeias

Abstract: No Abstract as this is an Editorial Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…The survey data suggests that the introduction of exotic species into the local pharmacopoeia of a studied community may involve the need for therapeutic diversification, or the desire to extend the spectrum of treated disorders in the community by using exotic plants [ 3 , 30 ]. Thus, the phenomenon of acculturation, or the loss of knowledge, discussed by Caniago and Siebert [ 12 ] can be seen as an adaptive response to environmental changes and/or a search for new chemical compounds [ 13 ] and not simply a process of loss of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey data suggests that the introduction of exotic species into the local pharmacopoeia of a studied community may involve the need for therapeutic diversification, or the desire to extend the spectrum of treated disorders in the community by using exotic plants [ 3 , 30 ]. Thus, the phenomenon of acculturation, or the loss of knowledge, discussed by Caniago and Siebert [ 12 ] can be seen as an adaptive response to environmental changes and/or a search for new chemical compounds [ 13 ] and not simply a process of loss of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothesis of diversification predicts that the inclusion of exotic plants diversifies a local therapeutic repertoire, contributing to the treatment of a broader range of therapeutic targets and, in some cases, treats diseases which native species do not [ 1 , 3 ]. Thus, treating the incorporation of exotic plants into a pharmacopoeia as acculturation and/or loss of knowledge should be viewed with caution because this perspective often ignores the fact that knowledge systems are dynamic and may contain strong adaptive components [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the number of useful herbaceous species was higher in teak than in mahogany and non-rehabilitated stands. Tropical primary forest is usually considered most important for traditional plant collectors, but as pointed out by Stepp and Moerman (2001), the use of plants growing in disturbed sites have often been overlooked as well as the use of new exotic plants (Medeiros, 2013). We found that exotic species was mainly used for food and annual species for fodder.…”
Section: Number Of Useful Plant Speciesmentioning
confidence: 65%
“…role in traditional plant collection (Stepp & Moerman, 2001). For plants with more general uses as food, fodder or construction, people often show flexibility and learn to use new species, or start using species that became common as a result of forestry (Medeiros, 2013). These species, often exotic, may therefore be more common in the rehabilitated stands.…”
Section: Introductionmentioning
confidence: 99%
“…This could be favored by the decreasing availability of native resources and the strong influence of external government organizations which provide technical support that promotes the incorporation of exotic resources (Eyssartier et al, 2013). The use of exotic species in domestic landscapes in Patagonia and other regions of the world has been highlighted by several authors to be a local solution to various needs, since in general they are easily available, fast growing, and more tolerant than native species (Eyssartier et al, 2009;Dos Santos et al, 2010;Richeri et al, 2013;Rovere et al, 2013), in addition to complementing native species, covering new needs, and diversifying the offer of useful plants (Albuquerque, 2006;Medeiros, 2013;Ladio and Albuquerque, 2014). The semi-domesticated landscape, which includes mainly river valleys, with an intermediate level of human intervention, was also a significant site for the gathering of firewood.…”
Section: Discussionmentioning
confidence: 99%